Reparations: between the military defeat of the shining path and democratic frustration - Dávila, Deici (2018)
The period of political violence that engulfed the country between 1980 and 2000 left deep wounds in thousands of Peruvians and uncovered grave social debts. The war declared by The Shining Path mobilized State forces which caused severe violations of human rights, not only between both sides, but also within civilians. Social agitations and the strategy of police intelligence put an end to the violence, but the fujimorismo political sector and the armed forces attributed the victory to themselves. Meanwhile, hundreds of thousands of victims cried for justice. In order to achieve social reconciliation, institutions such as the Truth and Reconciliation Committee recommended that the State begin enacting reparations through social programs. However, a series of factors have prevented these from being effective.